(untitled) (REICE: Revista Electrónica de Investigación en Ciencias Económicas, 2017)
The present study aims to evaluate the relationship between Nicaraguan exports and the evolution of the Real Exchange Rate (TCR). Quantitative techniques and monthly time series were applied for the period 2006-2016. The results indicate that through the VAR model, it is possible to verify that the variable real exchange rate has a significant impact on Nicaraguan exports. However, the magnitude of the impact will depend to a large extent on the trade policy adopted by Nicaragua to promote a level of market diversification and export products.